Application of thermal energy storage with point focus Fresnel lens concentrator: Numerical and experimental analysis. (December 2019) - Kaddoura, Mustafa F.; Zeaiter, Joseph
Highlights: Design optimization of a cavity receiver for use with a point focus Fresnel solar concentrator. Computational fluid dynamics model developed to assess temperature distribution inside the receiver. Simulation results were validated against experimental data at different HTF flowrates and irradiation intensities. The amount of thermal energy stored in June for Lebanon was expected to reach 7.2 kWh/m 2 .day. Abstract: The design of a solar cavity receiver was examined with the help of a developed mathematical model to determine thermal performance and seasonal energy storage. CFD simulation for fluid flow and radiation transport were conducted to analyze heat transfer in the optimized geometry. Modeling results were validated experimentally in outdoor conditions using eight different heat transfer fluid flow rates and four solar irradiation values ranging between 500–1000 W/m 2 . The model was used to predict the thermal efficiency of the receiver, the outlet temperature of the heat transfer fluid and the thermal energy storage during each month of the year. The analysis demonstrated the ability of the laboratory-scale Fresnel lens to increase the temperature of the heat transfer fluid by 200  ∘ C. The amount of thermal energy stored is expected to range between 2 and 7.2 kWh/m 2 per day during winter and summer respectively, with a thermal efficiency ranging between 93.6% and 97.2%.